Gamma Spectroscopy Response Analysis of Bismuth Germanium Oxide (BGO) and NaI (Tl) Detector to Determine the Detector Efficiency using the Monte Carlo MCNPX Method - Oktajianto, Hammam; Setiawati, Evi; Richardina, Verry (JURNAL SAINS DAN MATEMATIKA, 2015)
Simulation of Gamma spectroscopy with Bismuth Germinate Oxide (BGO) and NaI(Tl) detectors has been done using Monte Carlo method in MCNPX computer program. Simulation was conducted by modelling detector scintillator geometry, model of radiation source which was Cobalt-60 and pulse count model. BGO and NaI(Tl) had a diameter of 3 inch and thickness of 3 inch and closed by Aluminium with 0.05 cm thickness. Extended radiation source of Cobalt-60 was in radius of 0.15 cm which was put in front of detector surface with distance of 0.001 cm, 2 cm, 4 cm, and 12 cm. The simulation results showed that the less radiation count with increasing distance of the radiation source which was put in front of detector. Reduce of the radiation count lead to decrease efficiency in each increase of radiation source distance. The detector efficiency to count gamma ray radiation of BGO detectors was better than NaI(Tl) detector. The maximum efficiency of both detectors was occurred at distance of 0.001 cm in front of detector. These results also showed that MCNPX was able to agreeably simulate detector process to determine spectroscopy Gamma response.